Comprehensive Self-Management of Heart Failure - Shunsuke Kiuchi; Shigeto Tsukamoto; Rie Sato; Keisuke Hosono; Jun Okuda; Makoto Natsumeda; Mitsuharu Kawamura; Hideaki Tachibana; Takashi Okada; Takuro Takagi; Yasushi Taniguchi; Jiro Ando; et al. (Journal of Cardiovascular Development and Disease)
In response to the heart failure (HF) pandemic, it is important to introduce appropriate pharmacological and non-pharmacological treatments for HF patients. In addition, self-management of HF, including the continuation of appropriate pharmacological treatment, is also important. There have been many reports on self-management of HF. However, the effectiveness of patient education of HF is not consistent. One of the reasons may be whether the tools used are common or not. Moreover, unified systems of HF patient education and disease management in metropolitan areas are rare. We began joint HF patient education and disease management in the Tokyo southern medical district (JONAN Heart Failure Medical Collaboration: JHFeC). Patients undergo a multidisciplinary HF education program at JHFeC member hospitals to ensure that they are able to adequately record information on the self-management sheet. After discharge, the continuity of self-management will be evaluated, and further education will be provided if necessary. HF patient education is important even in severe HF requiring a left ventricular assist device, and such patient education needs to be provided appropriately in all manner of HF patients with stage A to D.